Entrepreneurship Skills and Career Performance Among Self Employed University Graduate in the North West of Nigeria - Sani, Amina; Shika, Maimuna Aliyu (NIU Journal of Social Sciences, 2017)
Human capital theory was used to examine the effect of entrepreneurship skills on career performance. A total of 319 self-employed university graduates in the northwest geopolitical zone of Nigeria participated in the study. The present study also employed a cross sectional research design in which data was collected and analysed within a short period of time. Results using partial least squares structural equation modeling (PLS-SEM) supported the hypothesized direct effect of entrepreneurship skills on career performance. However, the hypothesized significant relationship between financial management skill and career performance was not found. Theoretical, methodological and practical implications are discussed. In particular, the results recommended that entrepreneurship skills acquired through the mandatory entrepreneurship education programme for undergraduate students of tertiary institutions in Nigeria are an important consideration in helping self-employed graduates to enhance their career performance.